1973
DOI: 10.1099/00221287-78-2-349
|View full text |Cite
|
Sign up to set email alerts
|

Temperate Bacteriophages for Streptomyces coelicolor A3(2) Isolated from Soil

Abstract: S U M M A R YThree phages, isolated from soil samples collected in different localities, produced turbid plaques with a characteristic morphology on Streptomyces coeZicoZor ~3 ( 2 ) . Surviving growth from the plaques was lysogenic: when isolated and purified it was resistant to lysis by the homologous phage and released phage at a low frequency during growth. The three phages were homoimmune. The chromosomal attachment site of one of the prophages, VP5, was mapped in a position between hisE and cysD -that is,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

1978
1978
1984
1984

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…The fact that these lose their ability to lysogenize sensitive cells but are still unable to lyse strains carrying the wild-type prophage suggests, by analogy with phage h (Hershey, 1971), that these mutations affect some steps of the lysogenization process. Similar mutants have been isolated from the S. coelicolor A3(2) temperate phages $C3 1 and VP5 (Lomovskaya et al, 1970;Dowding & Hopwood, 1973). However, clear-plaque mutants of Bacillus subtilis phage SP10, which does not establish a stable relationship with the host, were reported (Kawakami & Landman, 1968).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The fact that these lose their ability to lysogenize sensitive cells but are still unable to lyse strains carrying the wild-type prophage suggests, by analogy with phage h (Hershey, 1971), that these mutations affect some steps of the lysogenization process. Similar mutants have been isolated from the S. coelicolor A3(2) temperate phages $C3 1 and VP5 (Lomovskaya et al, 1970;Dowding & Hopwood, 1973). However, clear-plaque mutants of Bacillus subtilis phage SP10, which does not establish a stable relationship with the host, were reported (Kawakami & Landman, 1968).…”
Section: Discussionmentioning
confidence: 96%
“…Lomovsks?ya et al (1972) and Dowding & Hopwood (1973) observed that only a few per cent of S. coelicolor A3(2) spores plated gave rise to colonies releasing phage. The fact that about 30 to 40% of the R7 cells plated produced colonies releasing phage may be explained in terms of the faster growth of the lysogenic strain than the sensitive strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phages for many bacterial genera may be readily isolated from most soils by enrichment of the soil with the potential host (Adams, 1959;Billing, 1969;Willoughby et al, 1972;Dowding, 1973;Dowding & Hopwood, 1973;Zachary, 1974), with nutrients (Reanney & Marsh, 1973;Casida & Liu, 1974;Tan & Reanney, 1976;Germida & Casida, 1981) or with both host and nutrients (Newbould & Garrard, 1954;Retinskaya & Rautenstein, 1960). Phages thus isolated have been widely used in biochemical, genetic and taxonomic research.…”
Section: Introductionmentioning
confidence: 99%